Validations on satellite based potential fishing zone advisories along Goa, south-west coast of India - Sreekanth, G. B.; Subramanian, S.; Manju Lekshmi, N.; Madhu, V. R.; Maria Fernandes, Passta; Singh, N. P. (Indian Journal of Fisheries, 2016)
The annual harvestable marine fisheries potential of Goa is estimated to be about 1.5 lakh t of which 50% is exploited. Potential fishing zone (PFZ) forecasts based on remotely sensed chlorophyll concentration and sea surface temperature are being applied for harvesting marine fishery resources. In this context, a validation study was carried out to analyse the effectiveness of PFZ advisories for Goa coast by 290 simultaneous purse-seine fishing experiments in PFZ and non-PFZ regions. A total of 290 feedbacks were collected from 290 fishing experiments within and outside the PFZ region with similar capacity vessels during 2006-2012. There was 50% reduction in scouting time for the purse-seine fishing which utilised the PFZ advisories. Purse-seiners were benefitted with a significantly higher (p